Quasi-active thermal control in LED street lights - Trofimov, Yu.V.; Lishik, S.I.; Pershukevich, P.P.; Tsvirko, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
In this paper, the hollow heat sink has been studied. The physical and mathematical model of a hollow heat sink and CFD modeling are proposed for fitting the experimental results. It has been shown that the model of a hollow heat sink allows to calculate the velocity (and temperature) of the air flow coming out of the hollow heat sink, to determine its dependence on the angle of the dissipated thermal power, length, and degree of fin and cross-sectional area of the hollow heat sink. The influence of the geometry of the inlets/outlets on the heat removal was analyzed. It has been shown that the efficiency of the quasi-active system increases significantly in the presence of external wind through the so-called “effect of spray”